The Shepherd - Forsyth, Frederick (Random House Group, 1975)
It is Christmas Eve, 1957. Flying home, on leave from Germany, a pilot is on a solo flight in the cockpit of a De Havilland Vampire. Sixty-six minutes of flying time, with a landing destination in England. No problem, all routine procedures. But suddenly, out the ocean, fog begins to close in, radio contact ceases and the compass goes haywire. When all hope is lost, out of the mist appears a World War II bomber, flying just below the Vampire, as if trying to make contact...
Keywords: Fiction